Molecular insights into Parkinson's disease - Thomas, Bobby (Faculty of 1000 Ltd, 2011)
Parkinson’s disease is a neurodegenerative movement disorder characterized by loss of midbrain dopaminergic neurons leading to motor abnormalities and autonomic dysfunctions. Despite intensive research, the etiology of Parkinson’s disease remains poorly understood leaving us with no effective therapeutic options. However, the recent identification of genes linked to heritable forms of Parkinson’s disease has revolutionized research in the field and has begun to provide new clues to disease pathogenesis. Here we discuss these recent genetic advances and highlight their significance in our quest to better understand common underlying disease mechanisms that will help us identify innovative neuroprotective therapies for Parkinson’s disease.